PENGARUH KEPEMIMPINAN VISIONER DAN MOTIVASI KERJA TERHADAP DISIPLIN KERJA GURU MADRASAH KABUPATEN KAYONG UTARA - Yuslianto Yuslianto; Aunurrahman Aunurrahman; Sukmawati. Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract:This study aims to determine the effect of visionary leadership and work motivation on the work discipline of Madrasah teachers in Kayong Utara Regency. This research is a quantitative study with data collection using a tool or instrument in the form of a questionnaire or questionnaire. The subjects of this study were all Madrasah teachers in North Kayong Regency, amounting to 60 people. Based on data analysis: (1) the visionary leadership of the principal has a significant effect on teacher work discipline that is equal to 23.2%, (2) the picture of teacher work motivation has a significant effect on teacher work discipline that is equal to 21.2%, (3) the picture of leadership visionary principals and work motivation together have a significant effect on teacher work discipline that is equal to 45.2%. The conclusions in this study are as follows: (1) visionary leadership significantly influences the work discipline of Madrasah teachers in Kayong Utara Regency, ( 2) work motivation significantly influences the work discipline of Madrasah teachers in Kayong Utara Regency, (3) visionary leadership and work motivation together have a significant effect on Madrasah teacher work discipline in Kayong Utara Regency. Keywords: Visionary, Work Motivation, Work Discipline.